The Law and the regulatory agencies in the provision of health care services at the local government level (1997)
In Nigeria, the Local Government is the third tier of government. It is the nearest organ to the people . In discharging its functions, there are some legislation that imposes some duties on their tier of government. One major function of the local government is the delivery of good health care services. These functions can only be effectively carried out, if the local government officials work together with different regulatory agencies that deal with different aspect of health services. This paper examines that various laws relating to health services at the local government level, discusses the regulatory agencies involved in implementing the laws , high-lights how efficient the laws and agencies have been . Part of the recommendations made on how to improve the health care services at the local government level include the active association in disseminating information with health rules: organizing enlightenment campaigns in vernacular ,languages , using local and indigenous ways of disseminating information on relevant health care services to the people , and for local government official go keep them abreast with current laws on health care services.